Analyst firm parent–subsidiary relationship and conflict of interest: evidence from IPO recommendations. (27th March 2012) - Lee, Cheolwoo
Abstract We uncover a new source for the conflict of interest in analyst coverage existed before the Regulation FD period by examining whether recommendations within the parent–subsidiary (PS) relationship are more optimistic and whether they have better investment value than non‐PS recommendations. We find evidence consistent with the conflict of interest: PS analysts on average issue more optimistic recommendations, but their recommendations have worse or no better investment value in the calendar‐time portfolio analysis. Analyst firm PS relationship is another source for the conflict of interest in analyst coverage that has not been identified before.